Integrasi Technological Pedagogical Science Knowledge pada Nilai-Nilai Islam - Laksono, Pandu Jati; Isnaini, Muhammad (Bestari, 2022)
TPASK is to represent science in information technology and education. Combining knowledge content, science content, technology content and pedagogical content is something that a student must have in their learning. Islamic religious perspective, education (pedagogy), science and technology are things that develop to make it easier for a believer to live his life. The method used in this research is library research or known as literature study. The method used is to analyze books, research results, and articles and then reduce them and present them to make new findings. Qualitative data analysis consists of four steps that occur simultaneously, namely categorization, data reduction, data presentation, and conclusions. The results of the review show that TPASK in the process must demonstrate Islamic values. Islamic values are closely related and strengthened with technology, pedagogy and science which are the basic concepts of TPASK. Another thing that strengthens the existence of Islamic religious values is an educational system that has character and religious values. Overview Integration is important because of the context that science, pedagogy, technology and religion are mutually reinforcing.